Odpowiedź:
a) 8 + 6 • x - 5 - 2 • x = 4 • x + 12 - 9 • x
6 • x - 2 • x - 4 • x + 9 • x = 12 - 8 + 5
9 • x = 9 /: 9
x = 1
Spr. : L = 8 + 6 • x - 5 - 2 • x = 8 + 6 • 1 - 5 - 2 • 1 = 8 + 6 - 5 - 2 = 14 - 5 - 2 = 9 - 2 = 7
P = 4 • x + 12 - 9 • x = 4 • 1 + 12 - 9 • 1 = 4 + 12 - 9 =
16 - 9 = 7
L = P
b) -4 - 5 • x + x + 6 = 7 - 2 • x + 9 - 4 • x
-5 • x + x + 2 • x + 4 • x = 7 + 9 + 4 - 6
2x = 14 /: 2
x = 7
Spr. : L = -4 - 5 • x + x + 6 = -4 - 5 • 7 + 7 + 6 = -4 - 35 + 7 + 6 = -39 + 7 + 6 = -32 + 6 =
= -26
P = 7 - 2 • x + 9 - 4 • x = 7 - 2 • 7 + 9 - 4 • 7 = 7 - 14 + 9 - 28 = -7 + 9 - 28 = 2 - 28 = -26
L = P
Pozdrawiam.